STABILITY INDICATING HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS DETERMINATION OF CEFPODOXIME PROXETIL AND OFLOXACIN IN ITS DOSAGE FORMS - PRASHANT D. GHODE; DR. SUNIL P. PAWAR (International Journal of Pharma and Bio Sciences, 2015)
A simple, precise, sensitive, reproducible stability indicating Reverse Phase High Performance Liquid Chromatographic method for determination of Cefpodoxime Proxetil and Ofloxacin in tablet dosage form was developed. Chromatographic separation was achieved on Hypersil-keystone RP C18 column maintained at 30ºC. Mobile phase consisting of buffer Potassium dihydrogenphosphate: Methanol: Acetonitrile (pH 3.0) in the ratio of 50:30:20v/v was pumped into the column at a flow rate of 1.2 ml/min. Determination was carried out at 235nm. Two peaks were obtained for Cefpodoxime at 13.1 min and 14.1 min and one peak for Ofloxacin at 5.11 min. The linearity was found to be 4-20 µg/ml and 10-50 µg/ml for Cefpodoxime for Ofloxacin respectively. Method was validated as per ICH guidelines. Cefpodoxime and Ofloxacin were subjected to various stress conditions including acidic, alkaline, oxidation, photolysis, reduction and thermal degradation. The proposed method can be extended to the analysis of Cefpodoxime and Ofloxacin in tablet dosage formulations.